The use of natural polymers for treatments enhancing sowing material - Korbecka-Glinka, Grażyna K; Wiśniewska-Wrona, Maria; Kopania, Ewa (Polimery, 2021)
Biopolymers from a group of polysaccharides are used in treatments enhancing sowing material of crops due to their physical and chemical properties, susceptibility to chemical modification, biodegradability and high bioactivity. Natural polymers, such as: chitosan, alginian, celulose, galaktoglucomannans, lignin and gellan gum, can be used as binders in seed coating or carriers of active substances and microorganisms. Moreover, biopolymers contained in the seed coatings and seed dressings can protect germinating seeds from unfavorable influence of environment and pathogens.